Optimalisasi Pengaplikasian BIPO dalam Pengelolaan Data Crew di PT Pelita Global Logistik - ST. Falihah.M; Annisa Rahmah; Laode Hibay Umar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
PT. Pelita Global Logistik is one of the shipping companies in Indonesia engaged in the transportation of dry bulk commodities. This study aims to analyze the optimization of the use of the BIPO application in crew data management at PT. Pelita Global Logistik. The research method used is a qualitative approach through observation, documentation, and interviews with relevant personnel in the crewing department. The data analysis technique employed is qualitative analysis, with PT. Pelita Global Logistik, headquartered in South Jakarta, as the unit of analysis. The results of the study indicate that the application of BIPO is able to optimize crew data management, improve administrative efficiency and data accuracy, and support more integrated monitoring of seafarers’ documents and certifications.